Effect of fire flame exposure on basalt and carbon fiber-reinforced concrete - Abd Razak, S.N. (Springer Science and Business Media Deutschland GmbH, 2021)
Damage of concrete in fire varies according to the nature of fire, mix proportions and constituents of concrete. When concrete are caught in fire, it can suffer consequential damage. Lots of research has been conducted so far to assess the effect of fire towards concrete. Usage of fiber becomes one of the interest in this evaluation of fire performance because fiber not only enhance the mechanical properties such as, compressive and tensile strength, but fiber can provide additional durability which is preventing cracks. In this study, chopped basalt and carbon fiber are used as reinforcement in concrete and its performance are compared with normal concrete. This paper reported the performance of fiber-reinforced concrete of standard grade 20 and 40 when subjected to fire flame at 28 days. The effect of fire on fiber reinforced concrete covers changes taking place in cement paste, aggregates, fibers, as well as their interaction that result in changes of physical and mechanical properties of concrete specimens. A direct fire exposure test was developed to imitate real fire event. Concrete specimens were burnt at 1000 Â°C temperature for 90 min continuously. After burning, the specimens were cooled at ambient temperature before further testing. From the findings, it is found that G20 OPC specimens obtained the highest residual compressive strength. Likewise, G40 OPC + CF specimens also obtained high residual compressive strength. Apart from that, the occurrence of spalling and cracking is observed during the duration of the fire exposure and after. The study showed adding carbon fiber in concrete improved its properties and damages observed after fire exposure were minor as compared to basalt fiber. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.